Anti–PD-L1 antibody direct activation of macrophages contributes to a radiation-induced abscopal response in glioblastoma. Issue 5 (3rd December 2019) - Ene, Chibawanye I; Kreuser, Shannon A; Jung, Miyeon; Zhang, Huajia; Arora, Sonali; White Moyes, Kara; Szulzewsky, Frank; Barber, Jason; Cimino, Patrick J; Wirsching, Hans-Georg; Patel, Anoop; Kong, Paul; et al.
Abstract: Background: Most glioblastomas recur near prior radiation treatment sites. Future clinical success will require achieving and optimizing an "abscopal effect, " whereby unirradiated neoplastic cells outside treatment sites are recognized and attacked by the immune system. Radiation combined with anti–programmed cell death ligand 1 (PD-L1) demonstrated modest efficacy in phase II human glioblastoma clinical trials, but the mechanism and relevance of the abscopal effect during this response remain unknown. Methods: We modified an immune-competent, genetically driven mouse glioma model (forced platelet derived growth factor [PDGF] expression + phosphatase and tensin homolog loss) where a portion of the tumor burden is irradiated (PDGF) and another unirradiated luciferase-expressing tumor (PDGF + luciferase) is used as a readout of the abscopal effect following systemic anti–PD-L1 immunotherapy. We assessed relevance of tumor neoepitope during the abscopal response by inducing expression of epidermal growth factor receptor variant III (EGFRvIII) (PDGF + EGFRvIII). Statistical tests were two-sided. Results: Following radiation of one lesion, anti–PD-L1 immunotherapy enhanced the abscopal response to the unirradiated lesion. In PDGF-driven gliomas without tumor neoepitope (PDGF + luciferase, n =  8), the abscopal response occurred via anti–PD-L1 driven, extracellular signal-regulated kinase–mediated, bone marrow–derived macrophage phagocytosis of adjacent unirradiated tumor cells, with modest survival implications (median survival 41 days vs radiation alone 37.5 days, P  = 0.03). In PDGF-driven gliomas with tumor neoepitope (PDGF + EGFRvIII, n =  8), anti–PD-L1 enhanced abscopal response was associated with macrophage and T-cell infiltration and increased survival benefit (median survival 36 days vs radiation alone 28 days, P  = 0.001). Conclusion: Our results indicate that anti–PD-L1 immunotherapy enhances a radiation- induced abscopal response via canonical T-cell activation and direct macrophage activation in glioblastoma.